2016
DOI: 10.1021/acscombsci.6b00106
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Three-Component Synthesis of 2-Imino-1,3-Thiazolines on Soluble Ionic Liquid Support

Abstract: An efficient one-pot, three-component synthesis of 2-imino-1,3-thiazolidines and 2-imino-1,3-thiazolines using ionic liquid-tethered 2-aminobenzimidazoles was reported. The protocol includes reaction of ionic liquid attached 2-aminobenzimidazoles with isothiocyanates to afford isothioureas, followed by its base induced inter and intramolecular nucleophilic displacement reactions with 1,2-dichloroethane (EDC) which results in thiazolidine ring formation. In the next to the last step, the ionic liquid support wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Chen et al [82] reported a one-pot, three-component condensation reaction of substituted 2-aminobenzimidazoles, isothiocyanate and triethylamine using ethylene dichloride (EDC) as a solvent and formed 2-imino-1,3-thiazolidines and 2-imino-1,3-thiazolines (Scheme 24). In this protocol, 2-aminobenzimidazole adhered on ionic liquid (IL), then isothiocyanate proceeded with IL-anchored 2-aminobenzimidazole, yielding isothiourea which combined with 1,2-dichloroethene by inter-and intramolecular processes and generated 2-imino-1,3-thiazolidines.…”
Section: Ionic Liquid-assisted Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al [82] reported a one-pot, three-component condensation reaction of substituted 2-aminobenzimidazoles, isothiocyanate and triethylamine using ethylene dichloride (EDC) as a solvent and formed 2-imino-1,3-thiazolidines and 2-imino-1,3-thiazolines (Scheme 24). In this protocol, 2-aminobenzimidazole adhered on ionic liquid (IL), then isothiocyanate proceeded with IL-anchored 2-aminobenzimidazole, yielding isothiourea which combined with 1,2-dichloroethene by inter-and intramolecular processes and generated 2-imino-1,3-thiazolidines.…”
Section: Ionic Liquid-assisted Synthesismentioning
confidence: 99%
“…But there is no detailed review of the synthesis and biological activity of 4 Comparative study of various synthetic protocols [58][59][60][61][62][63][64][65][66][67][68][69] Fig. 5 Comparative study of various synthetic protocols [77][78][79][80][81][82][83][84][85][86] Topics in Current Chemistry (2020) 378:34 1 3 34 Page 8 of 90 hoping to inspire new and even more creative approaches for researchers ( Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Sun and co‐workers also developed a one‐pot synthesis of 2‐imino‐1,3‐thiazolidines on a soluble support using ionic liquid tethered 2‐aminobenzimidazoles, isothiocyanates, and 1,2‐dichloroethane. [ 17 ] Shehzadi et al in 2019 achieved the thiazolidine‐2‐imines through one‐pot four‐component reaction of aldehydes, amines, alkynes, and isothiocyanates using CuI/ZnII dual catalyst through an intramolecular 5‐exo‐dig hydrothiolation reaction of the in situ formed propargyl thiourea. [ 18 ] Based on our survey, it is the only straightforward route to obtain thazolidone‐2‐imines without utilizing beforehand prepared intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…In 1887, the Hantzsch thiazole synthesis using the condensation of α‐haloketones with thiourea was established . A few routes for the synthesis of thiazolidin‐2‐imines have been reported in the literature . Amongst them, a few important methodologies which have been recently developed are illustrated in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Dethe and co‐workers have reported a synthesis of thiazolidine‐2‐imines by a multicomponent reaction of imines, terminal alkynes and isothiocyanates in the presence of a chiral copper‐pybox complex as catalyst (Figure a) . Sun and co‐workers have developed a one‐pot synthesis of 2‐imino‐1,3‐thiazolidines and 2‐imino‐1,3‐thiazolines on a soluble support using ionic liquid tethered 2‐aminobenzimidazoles, isothiocyanates and 1,2‐dichloroethane (Figure b) . Very recently, Li and co‐workers have developed a synthetic route to thiazole‐2‐imines involving phenacyl bromide, amine and phenyl isothiocyanate with trypsin as a biocatalyst (Figure c) .…”
Section: Introductionmentioning
confidence: 99%